1990
DOI: 10.1037/0882-7974.5.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Goal instability and later life adjustment.

Abstract: A series of analyses on the goal instability personality construct, as measured by the Goal Instability Scale (GIS), was conducted to establish the construct validity of goal instability as it relates to older adults. This construct was derived from Heinz Kohut's psychology of the self. The sample consisted of a total of 157 voluntary early retirees representing a cross section of worker types from a manufacturing industry. In the first analysis, a series of confirmatory factor analyses supported the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 26 publications
0
34
0
2
Order By: Relevance
“…1 Consistent with theoretical properties and the study of hope, greater goal stability is associated with more optimal adjustment under times of duress and major life change (Robbins, Lee, & Wan, 1994;Robbins et al, 1990), self-reported competencies and outcomes (Lese & Robbins, 1994), and greater satisfaction with social and interpersonal relationships (Robbins, Lese, & Herrick, 1993). Furthermore, both goal stability and hope are believed to be healthy, socially appropriate manifestations of selfstrivings in contrast to more self-centered, narcissistic mannerisms.…”
mentioning
confidence: 51%
“…1 Consistent with theoretical properties and the study of hope, greater goal stability is associated with more optimal adjustment under times of duress and major life change (Robbins, Lee, & Wan, 1994;Robbins et al, 1990), self-reported competencies and outcomes (Lese & Robbins, 1994), and greater satisfaction with social and interpersonal relationships (Robbins, Lese, & Herrick, 1993). Furthermore, both goal stability and hope are believed to be healthy, socially appropriate manifestations of selfstrivings in contrast to more self-centered, narcissistic mannerisms.…”
mentioning
confidence: 51%
“…Test-retest reliability of .76, internal consistency of .77, and factorial stability are indicators of its strong psychometric qualities. Goal instability has been found to be a more generalized measure of difficulty (Robbins, 1989) than originally hypothesized but has strong convergent, divergent, and construct validity (e.g., Robbins, Payne, & Chartrand, 1990;Robbins & Tucker, 1986;Watson et al, 1988). In any case, Watson et al (1988) found the Goal Instability Scale to correspond to maladaptive measures of narcissism, including psychic distress and poor empathic regard.…”
Section: Self-scalesmentioning
confidence: 99%
“…The Goal Instability Scale has also demonstrated high reliability and identical factor structure among older adults as well (Robbins, Payne, & Chartrand, 1990). Speaking summarily, the Goal Instability Scale demonstrates strong psychometric properties as well as theoretically-expected relationships with other variables of interest.…”
Section: Superiority and Goal Instability Scalesmentioning
confidence: 99%